Implementation of the Amsilati Method to Improve the Qira'ah Skills of Students at Islamic Boarding Schools - Azizah, Nur; Firdaus, Sulton (Al-Fikru: Jurnal Ilmiah, 2025)
This study explores the application of the Amsilati method to improve the ability of santri (Islamic boarding school students) to read classical Islamic texts (maharah qira'ah) at the Riyadlus Sholihin Islamic Boarding School in Tiris, Probolinggo. The Amsilati method combines theory and practice with examples from the Qur'an to facilitate understanding. This study employs a descriptive qualitative approach using observation, interviews, and documentation techniques to collect data. The results indicate that the Amsilati method is effective in improving students' ability to read classical Islamic texts, particularly in terms of fluency and understanding of tajweed. However, challenges include limited teacher resources, limited learning time, and difficulties in consistently applying the method. The implications of this study suggest that the Amsilati method has great potential to improve the quality of education in Islamic boarding schools, particularly in Quranic recitation instruction. This research supports the Islamic education theory proposed by Ahmad Syafii Ma'arif, which emphasizes the integration of theory and practice in teaching to achieve more effective learning outcomes.